PENGARUH FINANCIAL LITERACY DAN RISK TOLERANCE TERHADAP INVESTASI SAHAM GENERASI Z DI ERA DIGITAL - Juniarti, Septiani; Oebit, Cut Edwina Safia; Yuliantini, Tine Yuliantini; Ayomi, Putri (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2024)
Purpose The aim of this research is to analyze the influence of financial literacy and risk tolerance on generation Z's stock investment interest in the digital era. Methodology This research includes survey research. The population in this study were Mercu Buana University students who were of productive age range (17-26 years) with a sample of 46 respondents. Data collection techniques were carried out through questionnaires. The data analysis techniques in this research are Instrument Testing, Structural Model or Hypothesis Testing (Inner Model), Measurement Evaluation (Outer Model) and Hypothesis Testing. Findings The research results show that: (1) Financial Literacy has a positive and significant effect on generation Z's investment interest in the capital market; (2) Risk Tolerance has a positive and significant effect on generation Z's investment interest in the capital market. Suggestion Advice to investors and generation Z who intend to invest, they need to pay attention to risks and understand finances.